Public and scientific-research activity of the professor V.Ye. Timonov - L. M. Soloviova (History of science and technology, 2018)
The article highlights the social, scientific, organizational and practical activities of Vsevolod Yevhenovych Timonov – a well-known railway engineer, hydraulic engineer, railway worker and constructor of ports and water routes. The knowledge and experience acquired by national scientists in the United States on the construction of canals and international forums were later successfully used in practical work in tsarist Russia V.Ie. Timonov and V.Ie. Lokhvytskyi participated in the reconstruction of a number of waterways of the country directly by the implementation while dredging works. The experience of foreign countries, primarily the United States, influenced the views of local hydraulic engineers. Massive remedial works, for example, on the Mississippi River, made it possible to increase its depth. That is why V.Ie. Timonov, who was well acquainted with such experience, became a strong supporter of the use of dredging technology on navigable rivers and theoretically proved the possibility and feasibility of using dredgers to provide the necessary depth for navigation. Thus, the foreign experience was directed by local engineers to the practical course of their activities. V.Ie. Timonov had an impeccable record. The diverse activities of the scientist testify the recognition of his authority in the scientific and administrative circles of the Ministry of Communications. Wherever he applied his knowledge and qualifications of an engineer, these were the most important areas of state policy in the field of water transport and hydraulic engineering. V.Ie. Timonov is the founder of the original direction in the construction industry, one of the founders of the doctrine of ports, the founder of the theory of the structure of hydraulic structures, the developer of the doctrine of port infrastructure and improvement of navigability of the great years, the historian of science and technology. Vsevolod Yevhenovych took one of the honorary places in the world of hydraulic engineering, water and partly rail transport. Established on the basis of his numerous and original works, as well as the works of his students, the patterns in the problems developed by him, made a significant contribution to the further development of hydraulic engineering, not only in our country, but also in the world. In the light of his original beliefs, he analyzed the previously accumulated scientific material and showed it in a new and correct coverage. His works, his ideas, theories and views revealed before the hydraulic engineering unprecedented opportunities previously available.